(3eLehY GdWQa hLGeY GdWQas
(3ChdgG (B:s
(3CeG HYO, deG cGfJ GdCMGOjK GdeSJWQaI, hGdCNHGQ GdeSJYPHI GdeSJXQaI, s
(3BNQgG (B:s
(3hEf SdeJ dj QRbJc, hEf CbHdJ bHdJc, hEf JHJ ZaQJ dc s
(3Vef eLehY , JQJjHgG (B: (3ef U (B108 - (3U(B282s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B186 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs